2010
DOI: 10.1016/j.bpj.2009.12.3445
|View full text |Cite
|
Sign up to set email alerts
|

α-Lactalbumin, Engineered to be Non-Native and Inactive, Kills Tumor Cells When in Complex with Oleic Acid: A New Biological Function Resulting from Partial Unfolding

Abstract: In addition to its function as an intermediate in nitrogen metabolism, the small molecule urea plays an important role in the homeostasis of osmolarity and fluid volume in many organisms, including mammals, which concentrate urea in the kidney to produce the osmotic gradient necessary for water re-absorption. Because urea is highly polar and consequently poorly permeable through lipid bilayers, specialized urea transporters have evolved to increase its rate of diffusion across cell membranes. To better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…We prepared BLAOA, a complex similar to BAMLET, using a simple incubation of BLA in the presence of OA under mild conditions favoring partial unfolding (Ca 2+ -depletion and 37 ºC) 22 . This approach provides the opportunity to A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 4 form BLAOA with varying amounts of OA included in the complex. Our subsequent analysis showed that both the complex ability to induce leakage and cell death correlated well with the amount of OA bound in the complex.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…We prepared BLAOA, a complex similar to BAMLET, using a simple incubation of BLA in the presence of OA under mild conditions favoring partial unfolding (Ca 2+ -depletion and 37 ºC) 22 . This approach provides the opportunity to A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 4 form BLAOA with varying amounts of OA included in the complex. Our subsequent analysis showed that both the complex ability to induce leakage and cell death correlated well with the amount of OA bound in the complex.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The phenomenon of cytotoxic protein-oleic acid (OA) complexes has received continuous attention in recent years, in particular HAMLET (Human -Lactalbumin Made Lethal to Tumors) and its related complexes [1][2][3][4][5] . Such complexes are more generally known as proteinfatty acid (PFA) complexes and the focus these have received are partly due to their possible A C C E P T E D M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H‐NMR spectrum of HAMLET exhibited broad peaks with poor chemical shift dispersion, indicating a protein in conformational exchange on the millisecond timescale. The NMR signals corresponding to oleic acid were detected in the spectrum and the signal was broader than oleic acid alone, suggesting that the fatty acid was integrated into the protein [2,31]. Recombinant wild‐type α‐lactalbumin, expressed in Escherichia coli , showed identical CD and ANS spectra as the native protein and was readily converted to HAMLET on an oleic acid‐conditioned column [2].…”
Section: Structural Aspects Of Hamlet‐type Complexesmentioning
confidence: 99%
“…From the fitting, the stoichiometry was determined to be ca. 5.2 and the dissociation constant (K d ) was ~2.5 x 10 -4 M. The stoichiometry value of 5.2 is in good agreement with 5.1 -5.4 for the HAMLET complex prepared by the original chromatographic method[4,10,30]. Meanwhile, the enthalpy change (ΔH) was -4.3 kJ/mol, the entropy change (T·ΔS) was 17.2 kJ/mol, and the Gibbs free-energy change was -21.5 kJ/mol.…”
mentioning
confidence: 54%
“…Removing the bound calcium ion induces changes in the tertiary structure of α-LA [7][8][9] to form a stable folding intermediate; a molten globule in which rigid tertiary structure is lost but native-like secondary structure is maintained [10,11]. Also, it was reported that addition of 7.5 equivalent of oleic acid to bovine α-LA (pH 8.3, 5 mM EDTA) at 20℃ induces the conformational changes resembling those observed in the formation of molten globule [12].…”
Section: Introductionmentioning
confidence: 99%